Peran Komunikasi Persuasif dalam Membentuk Kesolidaritas Antar Masyarakat Desa Air Kemuning Dusun III: Komunikasi Persuasif Desa Air Kemuning - Anissa Putri Zaini; Debi Febriansa; Nafysah Zahrah; Monica Wulandari; Tesa Septriani (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This article discusses the role of persuasive communication built by the community in forming solidarity between communities. The purpose of this research is to find out the forms of persuasive communication that build community solidarity in Air Kemuning Village. Persuasive communication is a psychological activity in an effort to influence the attitudes, traits, opinions, behavior of a person or many people carried out by means of communication based on arguments and psychological reasons. Solidarity is a sense of unity among individuals, groups or communities or an attitude of cooperation with one another. In social life, good persuasive communication is needed to support the occurrence of solidarity between its people. The better the persuasive communication actions carried out, the easier it will be for community solidarity to arise. The research method used is a literature study whose data collection is from observation, interviews, documentation. The results showed that persuasive communication in the Air Kemuning Village community can be formed from mutual cooperation activities and social care that can create solidarity with the surrounding community. Keywords: Communication; Persuasive; Solidarity; Community